An Analysis of the Damage of Cargo Pump Impeller with HCl Hydrochloric Acid Load on MT Cipta Anyer using the Hurber and Miles Method - Mahendra, Reno Putra; Kristiyono, Antonius Edy; Pribadi, Teguh; Robbi, Shofa Dai; Nugroho, Azis (Sekolah Tinggi Agama Islam Al-Furqan, Makassar - Indonesia, 2025)
The cargo pump is an auxiliary device used to transfer cargo from the ship’s tank to a storage tank. One of the most critical components of the cargo pump is the impeller, which functions by converting mechanical energy into kinetic energy to move fluid. Hydrochloric acid, as cargo, is highly corrosive and requires specialized materials resistant to such conditions. On the MT Cipta Anyer, the impeller is constructed from Hastelloy X Tantalum to withstand corrosion. This study employs the Huber and Miles method to analyze impeller damage. Data collection was conducted through observation, interviews, documentation, and literature review. The research findings reveal that the primary cause of impeller damage is exposure to the corrosive cargo. Additional contributing factors include the use of spare parts that do not conform to the manual specifications, damaged impeller blades, and contamination within the impeller unit. These issues result in a decreased cargo discharge rate, leading to operational inefficiencies and financial losses for the company. The problems can be mitigated by implementing a regular Planned Maintenance System (PMS), ensuring the availability of manufacturer-recommended spare parts, and adhering to standard installation procedures. This study contributes practical insights into the causes of impeller damage in cargo pumps handling corrosive materials and provides actionable solutions to improve equipment reliability and operational efficiency in chemical tanker operations.